GAMBARAN TOKOH UTAMA DALAM NOVEL DALAM DERAI HUJAN KARYA SANDRA BROWN - Asmarani, Rahmanti; Oemiati, Sri (Proceeding SENDI_U, 2017)
Those are taken from the reality, then those gathers with the theories to analyze the literary works. One of them is psychoanalytic literary criticism. Psychoanalytic literary criticism is usually used to analyze the emotions, psychological conflicts and the psychological phenomenon of a Derai psychoanalytic literary criticism. Some steps are conducted to gain the data, they are close reading, review and note taking. There are some techniques used to analyze the main character, and the results reveals that Ben Tierney, as leadership, charming and smart person. Keywords : literary works, main character, psychoanalytic literary criticism , psychological conflict